Motives for choosing the turn to a teaching career - Augustinienė, Aldona; Stanišauskienė, Vilija (Frontiers in Education, 2025)
IntroductionThe present study was conducted to address the lack of qualitative data on the motivations for pursuing a career in teaching. A strategically important aspect of the current and projected teacher shortage in many countries is the experience and skills that career changers bring to the educational environment. Research has shown a trend for specific prestige characteristics to dominate as an aspect of the attractiveness of the teaching profession. However, the prestige of the teaching profession is a dynamic phenomenon, and in many contexts worldwide, it is low or declining. Therefore, what motivates individuals from other career paths to become teachers and counterbalance the profession’s low prestige is a highly relevant and under-researched issue, as this understanding can help teacher educators address the expectations of career changers. The main aim was to identify the specific motivations that prompt individuals from diverse professions to pursue teaching as a career in a context of low professional prestige.MethodsQualitative data was gathered from 109 career-change teaching students (hereafter, CCTs). A reflexive thematic analysis of the motives of career-changing teachers revealed that intrinsic and altruistic motives align with the findings of other studies but differ in some aspects.Results and discussionThat is, their commitment to improving the world is inspired by the desire to contribute to enhancing education and to realise their perceived professional and personal potential without fear of professional challenges such as low popularity, relatively low salaries, and high responsibilities. CCTs’ motives for transitioning into teaching from other fields have revealed that teaching was a natural continuation of their previous careers, a way to contribute to the improvement of the educational system, a means to become part of an organization, and (in the case of emigrants) to join the ethnic community. The study concludes with recommendations and suggestions for career education specialists, teacher education institutions, and potential avenues for further research.